Dynamics and structure of a stratified flow around a horizontal plate - Zagumennyi, Ia.V. (Reports of the National Academy of Sciences of Ukraine, 2014)
Computations of the two-dimensional problem of a continuously stratified incompressible fluid flow around an impermeable obstacle are carried out by the finite volume method based on the package OpenFOAM and the own programs, by using high-performance cluster systems. The structure and the dynamics of the stratified flow around a horizontal plate are studied in a wide range of Froude and Reynolds numbers. The stratification effects have a significant influence on the dynamic characteristics of the flow and may even lead to a change in the sign of the integral lift force acting on plate's surface. In the extreme case of large Froude numbers, when the transition to the homogeneous fluid approximation occurs, the flow characteristics converge to a solution, in which a number of fine-structure components lose their individual properties and become indistinguishable.